EXPLORING THE INFLUENCE OF MONEY, FOMO, AND SELF-CONTROL ON GENERATION Z'S PERSONAL MONEY MANAGEMENT, MODERATED BY FINANCIAL AWARENESS - Widhya Sedana Putra P, Komang; Lasmi, Ni Wayan (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2024)
As the importance of personal money management becomes increasingly recognized in Indonesia, this research investigates the factors influencing Generation Z's financial behaviors. Specifically, it explores the impact of the love of money, Fear of Missing Out (FoMO), and self-control on personal money management, with financial awareness serving as a moderating variable. Employing a quantitative approach, the research utilizes a questionnaire to gather data from a sample of 100 respondents in Denpasar City, selected through the Slovin formula. The data is analyzed using the path analysis program Smart PLS 3.0. The findings reveal a positive correlation between the love of money, FoMO, and self-control with personal money management. Furthermore, financial awareness is identified as a moderator in these relationships. The study suggests that Generation Z should enhance their financial awareness to better prepare and manage their finances effectively. The insights gained from this research encourage regular personal money management to achieve focused and sustainable financial management.